The sources and determinants of productivity growth in the Malaysian Islamic banking sector: a non-stochastic frontier approach - Sufian, Fadzlan; Haron, Razali (Inderscience Publisher UK, 2008)
This paper investigates the performance of the Malaysian Islamic banking sector during the period 2001–2005. In the first stage, the productivity estimates of individual banks are evaluated using the nonparametric Malmquist Productivity Index (MPI). A multivariate analysis is employed in the second stage to determine factors that influence the productivity of the domestic Islamic Banking Scheme (IBS) banks, the foreign IBS banks and the full-fledged Islamic banks. The empirical findings suggest that during the period of study, the Malaysian Islamic banking sector exhibited progress in productivity, attributed to an increase in efficiency rather than to technological change. The empirical findings suggest that profitability and bank size have positive relationships with Malaysian Islamic banks' productivity, while capitalisation and market share exhibit negative relationships with it. The results also suggest that Malaysian Islamic banks that are more efficient are the ones that pay Zakat (annual levy on the wealth of a Muslim).